Towards New Metrics for the Characterisation of the Dynamic Performance of Adaptive Façade Systems - Lorenza Bianco; Ylenia Cascone; Stefano Avesani; Pascal Vullo; Timea Bejat; Stefan Koenders; Roel C.G.M Loonen; Francesco Goia; Valentina Serra; Fabio Favoino (Journal of facade design and engineering, 2018)
Traditional façade characterisation metrics such as U-value and g-value are of limited value in the design process of buildings with adaptive façades. This issue is particularly important for adaptive façade components that have the capability of controlling thermal energy storage in the construction thermal mass. Building performance simulations can help to analyse the performance of buildings with adaptive façades, but such studies usually only provide information about the energy and comfort performance at room level. Consequently, there is a need for development and testing of new façade-level performance metrics that can be used to compare the performance of different adaptive façade components. This paper presents experiences and lessons learned from four European R&D projects that have introduced novel metrics to capture the dynamic performance of adaptive opaque façades. Characteristics of the different metrics are described, and their similarities and differences are compared and contrasted. The paper highlights the main benefits of metrics that can capture dynamic effects, and concludes by providing directions for future work.